2009
DOI: 10.1109/tkde.2008.188
|View full text |Cite
|
Sign up to set email alerts
|

Fast Query Point Movement Techniques for Large CBIR Systems

Abstract: Abstract-Target search in content-based image retrieval (CBIR) systems refers to finding a specific (target) image such as a particular registered logo or a specific historical photograph. Existing techniques, designed around query refinement based on relevance feedback, suffer from slow convergence, and do not guarantee to find intended targets. To address these limitations, we propose several efficient query point movement methods. We prove that our approach is able to reach any given target image with fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In [12], authors confirmed that three-example queries are more effective than other numbers of examples; we will evaluate our method with different values of c.…”
Section: A Experiments Protocolmentioning
confidence: 90%
See 1 more Smart Citation
“…In [12], authors confirmed that three-example queries are more effective than other numbers of examples; we will evaluate our method with different values of c.…”
Section: A Experiments Protocolmentioning
confidence: 90%
“…The number of clusters is limited to a fixed number by using a clustermerging method. But this complex approach is unable to make effective use of the irrelevant examplesIn [12], authors propose a fast query point movement technique to adapt the target-search in CBIR. All above methods still have drawbacks including local maximum traps and slow convergence.…”
Section: Related Workmentioning
confidence: 99%